Medieval Garments Reconstructed : Norse Clothing Patterns - Fransen, Lilli (Book collections on Project MUSE., 2011)
Short introduction to the amazing finds of garments from the Norse settlement of Herjolfnes in Greenland by Else Ostergård. Chapters on technique: production of the tread, dyeing, weaving techniques, cutting and sewing by Anna Norgaard. Measurements and drawing of garments, hoods, and stockings with sewing instructions by Lilli Frandsen. A practical guide to making your own Norse Viking garment!